Transformational and System Model of managing the strategic dimension of the enterprise in the aspect of organizational culture diffusion - Machaczka, Krzysztof; Machaczka, Małgorzata (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
Today, one of the important areas of change is the process of adaptation in the field of organizational culture. The reason for this is the observed phenomenon of diffusion of cultures, which results from the confrontation of different patterns and forms of behavior not only of the members of the organization, but also the entire external dimension determined by the complex of socio-social factors of local markets in which enterprises operate and develop. This phenomenon leads to the necessity of starting processes aimed at reconfiguration of the solutions and organizational models used by enterprises, which will allow maintaining adequate coherence of their systems for building and maintaining development potential.